Bactericidal activity of oxacillin and glycopeptides against Staphylococcus aureus in patients with endocarditis: Looking for a relationship between tolerance and outcome - Papili Rita; Santucci Antonella; Cardaccia Angela; Vailati Francesca; Raglio Annibale; Soavi Laura; Ravasio Veronica; Stagni Giuliano; Moretti Amedeo; Pasticci Maria; Sgrelli Alessio; Pallotto Carlo; et al. (BMC, 2011)
Abstract Background There is no clear relationship between in vitro bactericidal activity tests and clinical outcome. We studied bactericidal activity of oxacillin, vancomycin and teicoplanin against Staphylococcus aureus isolates in patients with endocarditis and then we sought to determine if there was a relationship between in vitro bactericidal activity and clinical outcome. Methods Minimal bacteriostatic and minimal bactericidal concentrations were determined for Staphylococcus aureus strains isolated from patients with endocarditis following standardized methods. Medical records were reviewed retrospectively to collect data on antimicrobial susceptibility at admission, antimicrobial therapy, need for surgery, embolic events and outcome. Results and Discussion Sixty-two Staphylococcus aureus strains were studied in 62 patients with endocarditis. Overall, 91.9% definite, 21% methicillin resistant and 72.6% cured. Surgery was performed in 32.3% and embolic events were documented in 64.5%. Tolerance to oxacillin and teicoplanin was more common than vancomycin tolerance among methicillin susceptible Staphylococcus aureus. Among methicillin resistant Staphylococcus aureus teicoplanin was shown to have a higher rate of tolerance than vancomycin. No statistically significant differences on clinical outcome between oxacillin tolerant and oxacillin non tolerant Staphylococcus aureus infections were observed. Tolerance to oxacillin did not adversely affect clinical outcomes of patients with methicillin susceptible Staphylococcus aureus endocarditis treated with a combination of antimicrobials including oxacillin. The cure rate was significantly lower among patients with methicillin resistant Staphylococcus aureus endocarditis. Conclusions In vitro bactericidal test results were not valid predictors of clinical outcome. Physicians need to use additional parameters when treating patients with staphylococcal endocarditis.